2012
DOI: 10.1165/rcmb.2011-0115oc
|View full text |Cite
|
Sign up to set email alerts
|

Periostin, a Matricellular Protein, Plays a Role in the Induction of Chemokines in Pulmonary Fibrosis

Abstract: Idiopathic pulmonary fibrosis (IPF) is a chronic, progressive, and usually fatal form of interstitial lung disease (ILD). The precise molecular mechanisms of IPF remain poorly understood. However, analyses of mice receiving bleomycin (BLM) as a model of IPF established the importance of preceding inflammation for the formation of fibrosis. Periostin is a recently characterized matricellular protein involved in modulating cell functions. We recently found that periostin is highly expressed in the lung tissue of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
160
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 154 publications
(170 citation statements)
references
References 51 publications
8
160
0
2
Order By: Relevance
“…21 Further, periostin-deficient lung fibroblasts showed lower production of chemokines in response to TNF-a, accounting for the lack of inflammatory response in pulmonary fibrosis. 22 In a model of glioblastoma xenografts, periostin secreted by stem cells was found to recruit tumor-associated macrophages promoting malignant growth. 23 These studies are in accordance with our observations that lack or inhibition of periostin reduced the production of proinflammatory cytokines and the subsequent macrophage and lymphocyte infiltration to the injured kidneys.…”
Section: Discussionmentioning
confidence: 99%
“…21 Further, periostin-deficient lung fibroblasts showed lower production of chemokines in response to TNF-a, accounting for the lack of inflammatory response in pulmonary fibrosis. 22 In a model of glioblastoma xenografts, periostin secreted by stem cells was found to recruit tumor-associated macrophages promoting malignant growth. 23 These studies are in accordance with our observations that lack or inhibition of periostin reduced the production of proinflammatory cytokines and the subsequent macrophage and lymphocyte infiltration to the injured kidneys.…”
Section: Discussionmentioning
confidence: 99%
“…In animal and in vitro studies, Postn was shown to mediate pulmonary fibrosis by promoting the production of pro-inflammatory cytokines and inducing secretion of collagen by lung fibroblasts (38)(39)(40). In recent clinical studies, high serum Postn levels could predict a shortened survival and worsened outcome with increased fibrosis in patients with IPF (41).…”
Section: Periostinmentioning
confidence: 99%
“…Studies in a model of cardiac fibrosis indicated that periostin may act as a downstream mediator of Ang II signaling through complex interactions that involve p38/ CREB and erk/TGF-β pathways [14]. Additionally, lung fibroblasts from periostin-/-animals had an impaired response to TNF-α, and they failed to produce chemokines and pro-inflammatory cytokines, indicating that periostin could mediate both the inflammatory and the fibrotic process [15].…”
Section: Periostinmentioning
confidence: 99%